Industry 4.0: Lesson from multinational companies to manufacturing SMEs in Malaysia - Yacob, Peter; Krishnapillai, Gengeswari; Kwok, See Ying; Khor, Saw Chin (2017)
The manufacturing industry has to withstand an increasing global competition on product quality and production costs.Established manufacturing companies have recognized that customers are not willing to pay large price premiums for incremental quality improvements.As a consequence, many manufacturing companies adjust their production focusing on customized products and fast time to market.In order to cope with this challenge, industrial value creation must be geared towards sustainability. Currently, the industrial value creation in the early industrialized countries is shaped by the development towards the fourth stage of industrialization, the so-called Industry 4.0. This development provides immense opportunities for the realization of sustainable manufacturing. The aim of this study is to investigate the recent development and practice of Industry 4.0 in MNCs and provide empirical information on the potentials of implementing Industry 4.0 in SMEs. The present research will be conducted in twofold via sequential exploratory mixed method approach. The first (qualitative) phase will be examining MNCs in Malaysia who have successfully implemented the Industry 4.0. Upon understanding their experiences in implementing Industry 4.0, a research instrument will be developed which will be utilized in the second (quantitative) phase of the study. SME manufacturers will be investigated on their awareness and adoption issues pertaining to the Industry 4.0. The findings of this study expected to provide new directions and new practical insights in Industry 4.0 revolution practices in manufacturing SMEs in Malaysia. Policy makers will be facilitated in appropriately outlining the measures to plan, schedule and implement (1) drivers for the next horizon of operational effectiveness, (2) adapt new business models to capture shifting value pools, and (3) build the foundation for digital transformation.